The Transformation of the Cooperative Financial Mode in the Countryside of China and the Future Choice - Qiong Fu (SHS Web of Conferences, 2014)
As an important part of the financial system in the country, the cooperative finance for a long time is greatly promoted by the government to solve the problem of weak financial support in the countryside. For various reasons, it has not achieved many results, which reflects that only with government promotion it could not achieve success. Since 2003, some mutually-supported financial societies gradually gain the recognition from the government supervision agencies and gain a lawful status. However such cooperative agencies proceed very slowly with a lot of hindrance factors. Comparatively, some cooperative societies simultaneously organized by the peasants and some peasants financial mutual supporting agencies become active and become an important way to solve temporary financial needs of the farmers in the process of production, which also provide a possible way for the integration of various sources in the countryside. Such modes have achieved success in Japan and Korea, although in China they remain in the state of research. We need to establish a suitable way of financial cooperative system for the countryside in China on the bases of experiences of other countries.